2016
DOI: 10.1161/strokeaha.115.011360
|View full text |Cite
|
Sign up to set email alerts
|

Large Volumes of Critically Hypoperfused Penumbral Tissue Do Not Preclude Good Outcomes After Complete Endovascular Reperfusion

Abstract: R eperfusion therapy remains the mainstay of acute ischemic stroke treatment but its clinical benefit comes at the cost of potential harm from reperfusion injury leading to cerebral edema and hemorrhagic complications. Advanced computed tomography (CT) and magnetic resonance imaging (MRI) techniques have emerged as promising tools to improve treatment selection by excluding patients who are particularly prone to harm and have low chances of benefit. The term Malignant profile was originally proposed by the Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…However, for the most part, SWIFT-PRIME excluded patients with large volumes of severe hypoperfusion (Tmax >10 s >100 mL). It has been demonstrated that in the setting of limited baseline infarct cores, larger malignant hypoperfusion profiles were not associated with worse outcomes if successful reperfusion was achieved, and thus patients with Tmax >10 s >100 mL could still benefit from ET [16]. Another constraint of PIM selection is the inconsistency of perfusion imaging in identifying truly salvageable ischemic penumbra [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, for the most part, SWIFT-PRIME excluded patients with large volumes of severe hypoperfusion (Tmax >10 s >100 mL). It has been demonstrated that in the setting of limited baseline infarct cores, larger malignant hypoperfusion profiles were not associated with worse outcomes if successful reperfusion was achieved, and thus patients with Tmax >10 s >100 mL could still benefit from ET [16]. Another constraint of PIM selection is the inconsistency of perfusion imaging in identifying truly salvageable ischemic penumbra [17].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging acquisition parameters have been previously described. 6 This study was approved by the local institutional review board.…”
mentioning
confidence: 99%
“…The details of the perfusion protocol and post-processing pipeline were elaborated previously ( Dehkharghani et al , 2015a , 2016 ; Lima et al , 2016 ; Nogueira et al , 2016 ; Haussen et al , 2016a ); briefly, all perfusion imaging was processed using a commercial version of a vendor-independent software platform (RAPID version 4.5, iSchemaView, Menlo Park, CA, USA). Voxel-wise thresholding of tissue parametric perfusion maps was performed, including the time-to-maximum ( T max ) of the tissue residue function, which was computed to estimate the critically hypoperfused tissue volume at 6 s delay; cerebral blood flow (CBF, expressed in ml/100g/min) maps at default vendor thresholds of relative (r)CBF <30% of contralateral normal tissues were used for estimation of the irreversibly infarcted core , and the balance of the T max > 6s volume used as the putatively at-risk ischaemic penumbra volume.…”
Section: Methodsmentioning
confidence: 99%